Association between resting heart rate, metabolic syndrome and cardiorespiratory fitness in Korean male adults - Seol-Jung Kang; Gi-Chul Ha; Kwang-Jun Ko (Elsevier, 2017)
Background/Objective: The present study aimed to investigate the association between metabolic syndrome and cardiorespiratory fitness according to resting heart rate of Korean male adults. Methods: A total of 11,876 male adults aged 20-65 years who underwent health examinations from 2010 to 2015 at a National Fitness Centre in South Korea were included. Subjects' resting heart rate, cardiorespiratory fitness (VO2max), and metabolic syndrome parameters were collected. The subjects were divided into 5 categories (<60 bpm, 60-69 bpm, 70-79 bpm, 80-89 bpm, and ≥90 bpm) of resting heart rate for further analysis. Results: We found that elevated resting heart rate was positively associated with body mass index, systolic blood pressure, diastolic blood pressure, triglycerides, and fasting blood glucose levels (p < 0.001, respectively); in contrast, elevated resting heart rate was inversely associated with VO2max (p < 0.001). When resting heart rate of subjects was categorized into quintiles and analysed, the results showed that the relative risk of metabolic syndrome was 1.53-fold higher (95% CI, 1.34 to 1.82) in the range of 60-69 beats per minute (bpm), 2.08-fold higher (95% CI, 1.77 to 2.45) in the range of 70-79 bpm, 2.28-fold higher (95% CI, 1.73 to 3.00) in the range of 80-89 bpm, and 2.61-fold higher (95% CI, 1.62 to 4.20) in the range of ≥90 bpm, compared to those <60 bpm; this indicated that as resting heart rate increased, the relative risk of metabolic syndrome also increased. Conclusion: Resting heart rate of male adults was found to be associated with cardiorespiratory fitness; the risk factors for metabolic syndrome and relative risk of metabolic syndrome increased as resting heart rate increased.